Examining the Impact of Emotional Intelligence on Employee WellBeing and Employee Engagement in the Digital Era - Thapa, Pramila Pudasaini; Rana, Hari; Ucar, Özge; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2023)
Introduction: Employee Well-Being(EWB) and Employee Engagement(EE) are crucial for a healthy workplace, but concern about Well-Being (WB) and EE are still prevalent. Emotional intelligence(EI) can help regulate and recognize emotions. This study examines its impact on EWB and EE in the Digital Era(DE), considering sociodemographic factors. Methods: This study used self-administered survey to gather the data and combined a quantitative method with descriptive cross-sectional research design. Variety of tools, including the employee engagement scale (EES), which was used to assess EE, the emotional intelligence scale (EIS), which was used to measure EI, and the functional well-being score from the World Health Organization(WHO), which was used to measure EWB. These tools were validated and are reliable, as determined by Cronbach’s alpha and other statistical analyses. Results: The findings demonstrated that emotional intelligence (EI) significantly impacts employee well-being(EWB) and employee engagement(EE). H1 was accepted through Pearson correlation (P>0.005, R=0.065, R²=0.004, and adjusted R²=0.001), while H2 was supported by regression analysis (P>0.005, R=0.717, R² = 0.514, and adjusted R² = 0.512). These findings highlight that EI is a predictor of EWB and EE, as well as a factor associated with years of work experience. Conclusion: The findings suggest that EI plays a crucial role in determining EWB and EE. These results imply that developing and enhancing EI competencies could positively impact EWB and EE, thereby improving job satisfaction and organizational outcomes. Further research could explore the causal relationship between EI, EWB, and EE and identify potential interventions to enhance EI in the workplace.